Motivational Practices Used by Employers from the Satu Mare County: A Comparative Approach - Neagu, Olimpia; Teodoru, Mircea Constantin; Macarie, Simona (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The paper explores the motivation of human resources in the companies from Satu Mare County, through a comparison of employers’ and employees’ view. The comparison is based on data collected and processed within the project HURO/0901/264/2.2.2 implemented in partnership by "Vasile Goldiș" Western University and University of Debrecen and financed by European Union through ERDF under Hungary-Romania 2007-2013 Programme, in 2012, and on data collected and processed in 2013-2014, in a new field research applied to employees of 75 companies from Satu Mare County.